The expression of requesy found in Nanny McPhee and the Big Bang movie by Sussana White: Pragmatics Analysis - Wijayanti, Ika Ida; , Prof.Dr. Endang Fauziati, M. Hum; , Siti Fatimah, S.Pd.M.Hum (2013)
It is entitled The expression of Request found in Nanny McPhee and the Big Bang movie by Susanna White: Pragmatics Analysis. In this research, The researcher analyzes request expressions in Nanny McPhee and the Big Bang movie by Susanna White. The researcher chooses this study because she wants to enrich the discussion of request expressions viewed by pragmatic theory. The writer only focuses on the pragmalinguistics for request expressions, the illocution of request expression, and the request strategy in this movie. The object of this research is request expressions used in Nanny McPhee and the Big Bang (a family film) directed by Susanna White. The data of this research are sentences containing request expressions found in the movie. The researcher finds 118 request expressions in the movie. Data Source used in this research are taken from the movie. This movie contains many dialogues especially request expressions. The method of collecting the data in this research are watching the original Movie, note taking all the request expression in the movie, and re-typing all the sentences containing request expression in the movie. The writer uses descriptive interpretive to analyze the data of request expression in the movie. The techniques of analysis are finding out request expressions in the movie, identifying the pragmalinguistics of request expressions used in the movie, clarifying the intention of request expression used by the speakers in utterances in the movie and describing request strategies used in the movie. The result of the study has three main findings. First, the linguistics of the request are internal modification; Syntactic Downgrader (Question and Past Tense/ Negotion), Lexical/ Phrasal Downgrader (Politeness Marker, Hesitator), and external modification; preparators (preparing the speech act). Second, the researcher finds illocution of request. Third, request strategies of these findings are mood derivable, performative, obligation statement, want statement, suggestory, quire prepatory, and hint.